2014
DOI: 10.1016/j.appdev.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Is there a common pathway to maladjustment for internationally adopted and non-adopted adolescents?

Abstract: The main purpose of the research was to test whether cumulative effects represent a common pathway to behavioral maladjustment for internationally adopted adolescents and controls. The findings of previous comparison and follow-up studies have been contradictory. The hypothesis was tested in an original multi-informant study with 74 adolescents: 40 adoptees and 34 controls. The analyses of the data provided arguments in favor of the existence of a common pathway for adoptees and controls. The accumulation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In spite of adopted adolescents’ more difficult previous rearing experiences—e.g., loss, maltreatment, neglect [ 89 ]—the present study showed that the contribution of coercion/imposition and acceptance/involvement parenting practices to attachment security and aggressiveness was the same in these teens as in non-adopted counterparts. This result gives additional support to the idea of a common pathway to behavioral difficulties for adopted and non-adopted teens [ 59 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In spite of adopted adolescents’ more difficult previous rearing experiences—e.g., loss, maltreatment, neglect [ 89 ]—the present study showed that the contribution of coercion/imposition and acceptance/involvement parenting practices to attachment security and aggressiveness was the same in these teens as in non-adopted counterparts. This result gives additional support to the idea of a common pathway to behavioral difficulties for adopted and non-adopted teens [ 59 ].…”
Section: Discussionsupporting
confidence: 67%
“…The same variables that account for normative non-adopted adolescents’ outcomes can also explain adopted teens’ psychological development. In fact, there is some support to the idea of a common pathway to behavioral difficulties for adopted and non-adopted teens [ 59 ]; these authors observed that it was the aggregation of risk factors (IQ, attachment, and parenting) in adolescents and in their families, which was significantly related to maladjustment in both adoptees and non-adoptees. In the same vein, as it is the case in normative non-adopted adolescents [ 26 , 60 ], there is some evidence that secure attachment to adoptive parents can mediate the links between parenting styles and adopted children’s [ 61 ] and adolescents’ outcomes [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it could indicate the possibility that differences between adoptees and comparison adolescents are attributable to inter‐individual differences rather than to group differences because of the heterogeneity of the internationally adopted population (Lindblad, Weitoft, & Hjern, ). In fact, Roskam and Stievenart's () study provided arguments in favor of the existence of a common pathway to behavioral difficulties for adopted and nonadopted adolescents: it is the accumulation of risk factors (IQ, attachment, and parenting) in the current characteristics of the adolescents and their families that is significantly associated with maladjustment in both adoptees and nonadoptees.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conceptualization/measurement problem may be mentioned in Roskam and Stievenart's () study, which explored whether cumulative effects represented a common pathway to behavioral maladjustment for internationally adopted adolescents ( n = 40) and sociodemographically matched nonadopted counterparts ( n = 34). Attachment was identified as a risk factor, and no differences in attachment scores were found between adopted and nonadopted teens.…”
Section: Attachment In Adopted Adolescentsmentioning
confidence: 92%
“…In contrast, there is limited evidence that early maltreatment or institutionalization have long-term effects on adoptive individuals' attachment security within the adoptive parent-child relationship. Parents report few differences in the attachment behaviors of children adopted after experiencing adversity and non-adopted children [21][22][23][24][25], and adopted children and adolescents do not report feeling less security in their relationships with their parents than non-adopted children [26][27][28].…”
Section: Adoption and Attachment At Later Agesmentioning
confidence: 96%